Ethno-veterinary medicine perspectives of common diseases and health problems of livestock kept by rural women in South-West Nigeria: a case study (2010)
Ethnoveterinary medicine is the scientific term for traditional animal health care and provides low cost alternatives to use of modem veterinary services and drugs. Research into ethnoveterinary medicine is often undertaken as part of a community-based approach that serves to improve animal health and provide basic veterinary services in rural areas. The study applied some participatory, rural appraisal tools to identify common diseases and health problems among livestock kept by women formers in a case study rural setting in Southwest Nigeria as well as their ethnoveterinary practises and perception. Common livestock, diseases end health problems were ranked by respondents as Diarrhoea (26%), Newcastle Disease (22.7%), Mange (18%) fowl pox (8.4%) Pestes des petite ruminants (7.8%), Lice infestation (5.8%) foot and nose bots (5.2%), lick infestation (3.9%) and Contagious Caprine Plcuro pneumonic (1.95%). The farmers regard traditional intervention on the diseases of their animals as very effective as palliative treatment, and modern veterinary - services as curative but less accessible and very expensive. Veterinary staff associated with the community complained about non conducive working environment and lack of mobility/ambulatory vehicle, problems of quacks that have motorcycles and go around disguising as Veterinary doctors. Recommendations are-made for the training of some educated community members of community animal health workers, the control of quackery in rural areas, the provision of adequate mobility and conducive working environment for Veterinary staff as well as provision of veterinary services to farmers at affordable prices.